Efektivitas Penerapan Kurikulum Cinta dalam Mengembangkan Kecerdasan Emosional Anak Usi Dini - Satriani Junaid; Syahrul Saputra (Prodi PIAUD STAI AL-GAZALI BONE, 2025)
This study analyzes the effectiveness of implementing a love-based curriculum in developing emotional intelligence in early childhood. The study uses a library research approach with a descriptive qualitative type through the collection and review of scientific literature, including journal articles and books discussing affective education, emotional intelligence development, and love-based curricula. Data analysis was conducted using content analysis to identify the main themes related to love curriculum implementation strategies, emotional intelligence indicators, and supporting and inhibiting factors. The results showed that the love curriculum contributed significantly to improving children's self-awareness, emotional management skills, empathy, and social skills. The implementation of learning that emphasizes the values of love, affective communication, and warm interpersonal interactions has proven to be effective in building children's emotional intelligence as a whole. The synergy between teachers, learning media, and parental involvement is a key factor in the success of this curriculum. These findings emphasize the importance of integrating affective and spiritual values in early childhood education as the basis for character building and positive social relationships.